The Best Selection of PIP Scholarship: AHP-TOPSIS Vs Fuzzy AHP-TOPSIS. Issue 1 (March 2021) - Wardana, Ari Kusuma; Rianto,
Abstract: The Smart Indonesia Program (PIP) is a program created by the government to address education problems in Indonesia. Selection of students who are entitled to PIP assistance is the main problem in this study, so this study aims to provide a comparison and evaluation of the selection of students who are entitled to PIP assistance. Previous research has been evaluated using the AHP-TOPSIS method and in this study comparing the method between AHP-TOPSIS vs Fuzzy AHP-TOPSIS, the purpose of this study is to obtain the effectiveness of both methods. The criteria in this study are the impact of natural disasters, physical disabilities, the convict's family, PKH / KPS / KKS holders, destitute, orphans, parents' income and conflict areas. In this study, the results show that the two methods have the same ranking results, even though they have different weight values. This is because the importance value of each criterion is close together so that the results of the ranking of the two methods are the same. From these results, it can be concluded that the two methods are feasible to be used in the PIP scholarship selection, where the ranking of the choices is in alternatives 2 3 and 4.